2020
DOI: 10.3389/fbioe.2020.613986
|View full text |Cite
|
Sign up to set email alerts
|

Modeled Structure of the Cell Envelope Proteinase of Lactococcus lactis

Abstract: The cell envelope proteinase (CEP) of Lactococcus lactis is a large extracellular protease covalently linked to the peptidoglycan of the cell wall. Strains of L. lactis are typically auxotrophic for several amino acids and in order to grow to high cell densities in milk they need an extracellular protease. The structure of the entire CEP enzyme is difficult to determine experimentally due to the large size and due to the attachment to the cell surface. We here describe the use of a combination of structure pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 74 publications
3
8
0
Order By: Relevance
“…The structural fold of the N-terminal region was similar to the H-domain in PrtH (RMSD around 2.8 Å), whereas the C-terminal region was larger, with five longer helices. In the structure models, the C-terminal region had two different orientations, indicating a potential flexibility of the H-domain ( Figure 7 D) with the possibility to adopt more compact structures, as previously predicted [ 21 ]. The structural similarities in the H-domains suggested that these H-domains had similar functions.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…The structural fold of the N-terminal region was similar to the H-domain in PrtH (RMSD around 2.8 Å), whereas the C-terminal region was larger, with five longer helices. In the structure models, the C-terminal region had two different orientations, indicating a potential flexibility of the H-domain ( Figure 7 D) with the possibility to adopt more compact structures, as previously predicted [ 21 ]. The structural similarities in the H-domains suggested that these H-domains had similar functions.…”
Section: Resultssupporting
confidence: 70%
“…Fn2 β4–β5 orientated towards the active site with approximately 15 Å from the catalytic triad when Fn2 β4–β5 formed an extended β-turn structure or a β-hairpin. This region had also been proposed to be involved in substrate specificity [ 21 ]. However, Fn2 β4–β5 was much shorter in PrtP NFICC96H than in the other PrtP homologs, locating Fn2 β4–β5 further away from the catalytic cleft.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are secreted from the cell and anchored to the cell membrane, which ensures that proteolysis occurs close to the cell and allows efficient subsequent transportation. The catalytic domain contains the active site, composed of three amino acid residues (serine, histidine and aspartic acid) that are highly conserved across species (Hansen and Marcatili, 2020 ). The cell envelope proteinase from Lc.…”
Section: Fermentation Processesmentioning
confidence: 99%